2020
DOI: 10.1136/bmj.m2876
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating toxic stress in children affected by conflict and displacement

Abstract: Armed conflict and displacement pose a threat to the health and wellbeing of children. As the global community begins to recognize the cumulative effects of conflict and displacement related stressors, our attention has shifted to toxic stress and its short and long term health effects. 1 Toxic stress, regarded as the result of prolonged activation of the stress response, can occur before birth and during childhood is known to contribute to epigenetic changes, with health and neurodevelopmental consequences. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…First, there is an urgent need for investments in adolescent-responsive mental health services to support young people most at risk of depression and anxiety, given that more than 15% of the sample—and especially older girls—are experiencing moderate to severe symptoms of depression and anxiety. Community-based and online counselling services should be prioritized to support these young people, especially in host communities, where the risk of social isolation appears greater [ 106 , 107 ]. Given that more than a third of adolescents also reported that they lacked access to trusted peers and family members, and could therefore also be vulnerable to mental ill-health in the medium to longer term, investments in low-cost, peer-to-peer support groups that can be maintained through online and (physically distanced) in-person platforms during crisis episodes could be trialled.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is an urgent need for investments in adolescent-responsive mental health services to support young people most at risk of depression and anxiety, given that more than 15% of the sample—and especially older girls—are experiencing moderate to severe symptoms of depression and anxiety. Community-based and online counselling services should be prioritized to support these young people, especially in host communities, where the risk of social isolation appears greater [ 106 , 107 ]. Given that more than a third of adolescents also reported that they lacked access to trusted peers and family members, and could therefore also be vulnerable to mental ill-health in the medium to longer term, investments in low-cost, peer-to-peer support groups that can be maintained through online and (physically distanced) in-person platforms during crisis episodes could be trialled.…”
Section: Discussionmentioning
confidence: 99%
“…These environments have proven negative effects on ECD. [43][44][45] Pediatricians who work in conflict areas or where there are substantial numbers of refugee families should pursue training that equips them to care for the specific developmental needs of these children.…”
Section: Provide Additional Support For Marginalized and At-risk Chil...mentioning
confidence: 99%
“…However, others experience home as a hostile, violent space characterised by familial dysfunction (Judge, Ilies, and Scott 2006;Murray et al 2019). Equally, many young children are displaced from their homes, for example through conflict or migration (Ataullahjan et al 2020;Maldonado, Swadener, and Khaleesi 2019), often leading to experiences of exclusion and alienation (Mack 1993;Wahle et al 2019).…”
Section: Editorialmentioning
confidence: 99%
“…During the pandemic, while many parents will have provided astimulating home environment that has afforded young children high quality informal learning (Sylva et al 2010), this will not have been the case universally. Reasons may include lack of time, physical resources or space (Andrew et al 2020b; UNICEF 2020b), parents' lack of interaction with their young children (Hart and Risley,1995;Umek et al 2008), or increased toxic stress levied by confinement (Ataullahjan et al 2020). Moreover, the combination of setting and playground closures and mandates to stay at home have meant that young children have had fewer opportunities for outdoor play and free play (Gill and Munro 2020).…”
Section: Supporting Young Children's Informal Learningmentioning
confidence: 99%